An Einstein encyclopedia - Calaprice, Alice; Kennefick, Daniel; Schulmann, Robert J. (Gale virtual reference library, 2015)
This encyclopedia contains entries on Albert Einstein's life and work. Entries on Einstein's scientific theories provide background and context, along with details about his assistants, collaborators, and rivals, as well as physics concepts related to his work. Coverage of Einstein's role in public life includes entries on his Jewish identity, humanitarian and civil rights involvements, political and educational philosophies, and religion.